SELF-EFFICACY AS A MODERATOR: THE EFFECT OF INDUSTRIAL WORK PRACTICE EXPERIENCE ON STUDENTS' WORK READINESS - Pambudhi, Prawestri Yekti; Faslah, Roni; Swaramarinda, Darma Rika (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2024)
This research aims to assess the influence of industrial work practice experience on work readiness among students in vocational high schools, with self-efficacy as a moderating factor. This study focuses on 11th-grade students from the administration, accounting, and business programs at SMKN 2 Cikarang Barat during the 2023/2024 academic year. A quantitative methodology is employed, and the research encompasses 176 students as the sample size. For sample selection, the technique used is proportional stratified random sampling. The distribution of questionnaires employing a likert scale was selected as the method for data collection. The SmartPLS 3.0 software facilitated the analysis, including evaluations of both the Outer and Inner Model. This research's results substantiate that industrial work practice experience has a favorable and substantial effect on work readiness. On the other hand, self-efficacy is a moderating factor, significantly diminishing the positive connection between industrial work practice experience and students' work readiness.